Change of heart - Picoult, Jodi, 1966-; Poole, Nicole; Clark-Price, Stafford; Frangione, James; Ferland, Danielle; Ikeda, Jennifer (Prince Frederick, MD : Recorded Books, 2008)
Shay Bourne shattered June Nealon's life when he murdered her husband and daughter. Now, Shay wants to donate his heart to June's other, ailing daughter.
Compact discs.
Unabridged.
Narrated by Nicole Poole, Stafford Clark-Price, James Frangione, Danielle Ferland, and Jennifer Ikeda.
Keywords: Murderers -- Fiction; Death row inmates -- Fiction; Transplantation of organs, tissues, etc. -- Fiction; Repentance -- Fiction; Audiobooks